PENGARUH PENERAPAN E-AUDIT TERHADAP KINERJA AUDIT KEUANGAN DI BPK RI PERWAKILAN JAWA BARAT - Yanti Rufaedah (Jurusan Akuntansi Politeknik Negeri Bandung, 2017)
Abstract: Performance of BPK RI West Java Representative in audit of financial statements of entities using state budget, increasingly become a center of attention, because the audit result from this independent state institution also determining the credibility of its auditee. The expansion in the number of audited entities, along with the increasingly widespread regional autonomy climate, is much greater than the number of existing BPK auditors. This study aims to determine how much the Implementation of e-audit influenced the Performance Audit Finance by BPK auditors in BPK RI Representative of West Java. This study used primary data obtained through the distribution of questionnaires 50 BPK auditors as a representative sample of the total population of 100 people with purposive sampling technique. Simple Regression Analysis method was used to answer the problem and the hypothesis was tested with t-test. Weighted respondents' answers using Likert Scale with score range 1-5. The result shows that E-audit implementation have positive significant effect to Audit Performance of Financial Statement at BPK RI West Java Representative.Keywords: e-Audit, Financial Audit Performance